Clarification of the Relationship between the Magnetic and Conductive Properties of Infinite Chains in Trioxotriangulene Radical Crystals by Spin‐Projected DFT/Plane‐Wave Calculations. Issue 7 (8th June 2020) - Tada, Kohei; Kawakami, Takashi; Tanaka, Shingo; Okumura, Mitsutaka; Yamaguchi, Kizashi
Abstract: Approximate spin projection method and density functional theory with plane‐wave‐based calculations are combined to uncover and clarify the relationship between the magnetism and electronic conductivity of trioxotriangulene (TOT) radical crystals. The presented scheme exhibits an exceptionally high accuracy. It is clearly different from other techniques that have been conventionally used to calculate the magnitude of the effective exchange interaction ( J ) and the band structure of organic radicals. This enhanced performance is explained by these facts: i) the proposed scheme allows one to estimate band structures with electronic correlation between whole molecules in the crystal, ii) no crystal cutting‐induced artifacts and errors are introduced, and iii) both spin polarization and spin contamination are treated correctly. Consequently, the discrepancy between the experimental J value and the estimated value by the scheme equals 11.1 cm −1 . The scheme can be applied to the DFT‐D method, which is mostly considered for dispersion force. The collaboration allows discussions on the relationship between the magnetic and electronic properties, and the geometric structures. Moreover, it gives useful insights for the design of new functional organic materials. For example, the results of Br3 ‐TOT revealed by the approach better explains the previously reported but nonclarified properties of these species. Abstract : The relationship between the magnetism and electronic conductivity of trioxotriangulene radical crystals is uncovered by a new approach: approximate spin projection method combining density functional theory and plane‐wave‐based calculations (AP‐DFT/plane‐wave scheme). The accurate J value and band structure estimation allows for discussion of the relationship, and gain useful insights for the design of new functional organic materials.